Gastrointestinal pharmacology - Greenwood-Van Meerveld, Beverley (Springer, 2017)
"This volume aims to connect current ideas and concepts about GI disorders with the search for novel therapeutics. Towards this goal, authors provide a timely state-of-the-art overview of the GI tract in health and disease, current treatment approaches and ongoing developments in drug discovery, and their potential for the better treatment of patient swith GI disorders"--Publisher's description.
Keywords: Gastrointestinal agents.; Gastrointestinal system -- Diseases -- Chemotherapy.; elektronické knihy; electronic books